Two Rhetorical Models for Digital Da'wah to Youth: A Comparative Study of Habib Ja'far and Ustadz Hanan Attaki on YouTube - Andri Maijar; Latifahnum Fauza (INTERAKSI PERADABAN: Jurnal Komunikasi dan Penyiaran Islam, 2026)
This study compares the rhetorical styles of Habib Husein Ja'far Al-Hadar and Ustadz Hanan Attaki in their YouTube da'wah videos. Using Aristotle's Rhetorical Theory (ethos, pathos, logos), qualitative content analysis was applied to four selected videos—two per preacher—matched on religious and motivational themes. Results show that Habib Ja'far employs a narrative-philosophical rhetorical model: reflective storytelling, active hand gestures, and contextual social analogies, with a logos-dominant orientation that cultivates audience contemplation. Ustadz Hanan Attaki employs a popular-emotional model: accessible youth language, minimal gesture, Quranic reading as authority, and humor insertion, with a pathos-dominant orientation that motivates practical spiritual change. Despite shared qualities—casual attire, accessible language, and youth focus—their rhetorical paradigms diverge significantly. This study contributes a comparative typology of digital Islamic rhetorical styles and provides practical guidance for contemporary da'wah practitioners navigating the digital media landscape.